2011
DOI: 10.1021/ic1016627
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid-Enhanced Photooxidation of Water Using the Polyoxometalate Anion [P2W18O62]6–as the Sensitizer

Abstract: Simple polyoxometalate anions are known to be photoreduced in molecular solvents in the presence of 2-propanol or benzyl alcohol. The use of ionic liquids (ILs) as the solvent is now reported to also allow the photooxidation of water to be achieved. In particular, the photochemistry of the classic Dawson polyoxometalate salt K(6)[P(2)W(18)O(62)] has been studied in detail when water is present in the aprotic IL, 1-butyl-3-methylimidazolium tetrafluoroborate ([Bmim][BF(4)]) and the protic IL, diethanolamine hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 64 publications
2
45
0
Order By: Relevance
“…1). In a previous study, it was shown that photoreduction of ½P 2 W 18 O 62 6− does not occur in either bulk water or bulk DEAS (8). In the present two-phase configuration, the upper phase was water, in which K 6 ½P 2 W 18 O 62 is highly soluble, and the lower phase was DEAS, in which the salt is essentially insoluble.…”
Section: − Ilmentioning
confidence: 40%
See 4 more Smart Citations
“…1). In a previous study, it was shown that photoreduction of ½P 2 W 18 O 62 6− does not occur in either bulk water or bulk DEAS (8). In the present two-phase configuration, the upper phase was water, in which K 6 ½P 2 W 18 O 62 is highly soluble, and the lower phase was DEAS, in which the salt is essentially insoluble.…”
Section: − Ilmentioning
confidence: 40%
“…In recent studies, we have found that photoreduction of tetracyanoquinodimethane (TCNQ) to TCNQ − and ½P 2 W 18 O 62 6− to ½P 2 W 18 O 62 7− or more extensively reduced POMs occurs in "wet" ionic liquids (ILs) where water acts as an electron donor and is photo-oxidized to dioxygen (7,8 (Fig. S1) are summarized in Eqs.…”
mentioning
confidence: 99%
See 3 more Smart Citations